DELEGATION FROM USM VISITS RIKEN - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
On February 23, a delegation led by Vice-Chancellor Dato’ Omar Osman of Universiti Sains Malaysia (USM) visited RIKEN’s Wako campus. During the visit, Dr. Osman had discussions with RIKEN President Hiroshi Matsumoto, and researchers from the two institutions held fruitful talks regarding projects to be set up under the joint research center (USM-RIKEN International Center for Aging Science) established at USM last February following an agreement.